The Library Of Babble - Schanzel, Demi (Auckland University of Technology, 2020)
The Library Of Babble is a microcosmic social network, a practice-based endeavour designed through the use of the Self-determination theory, the Needs-Affordances-Features theory and the Values at Play methodology to imbue a collective sense of intimacy within its digital ecosystem. The ambitions of this project include critically engaging with emerging academic literature on the contemporary state of commercial social networks, and attempting to divine an alternative vision for digital communication through the use of explicit value-based frameworks. Developed over the course of eight months, the practice-based submission represents a critical perspective on the intersection of academic theory and theoretical modalities of interactive play, with the written submission acting as a testament to the grounding principles used throughout its development process. On booting up the Library of Babble, you're not asked for any form of identity-clarification or guided through the construction of a digital identity. You're simply greeted with a small simple message ("Love is one of the most important things on this planet" - anonymous) buried into the side of some abstracted geography, with no indication of authorship or immediate interaction. Besides the small psychedelic realm before you, the interface remains minimalist and almost brutalist in its absence of features, including only a few coordinates and a single mysterious compass. Using your keyboard to maneuver about you'll eventually discover other messages, each as anonymous and disconnected as the last. Simple testaments that others who have wandered through this space have felt inclined to leave behind. Stories and fragmented sentences which in combination with one another begin to express an intimate sense of humane reassurance and compassion, creating a space to feel safely open and explore one’s true self within.
Keywords: Social; Media; Networks; Video; Game; Virtual; Communication; Self-determination; Values at play; Selfhood; Immersion; Human-computer interaction